Margaret Chase Smith Library Student Essay Contest: Improving the American Educational System, Third Place Essay - Damon, Mariah (Maine Policy Review, 2013)
Each year, the Margaret Chase Smith Library sponsors an essay contest for high school seniors. In 2013, students were invited to propose what they would do to improve the American educational system.